2001
DOI: 10.1111/j.1460-2466.2001.tb02874.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Escapism: Predicting the Amount of Television Viewing by Need for Cognition

Abstract: Germans spend an average of more than 3 hours watching television each day. Among them, there are many who turn on their TV sets for less than 1.5 hours a day, and others who do this for more than 8 hours a day. What accounts for these differences? The central thesis in this paper is that individuals may be distinguished by their attitude toward thinking and that differences in their need for cognition explain the differences in their time spent with TV. The lower viewers' need for cognition is, the less pleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(73 citation statements)
references
References 13 publications
3
66
0
3
Order By: Relevance
“…Because television is often considered a nonveridical source of information (Shrum 2001), television messages may be viewed as weak arguments and thus counterargued rather than endorsed by those high in NFC. Moreover, research has found that NFC tends to be negatively correlated with television viewing (Henning and Vorderer 2001), and study 1 found a similar relation ( , ). Consequently, it is not comr p Ϫ.15 p !…”
Section: Resultsmentioning
confidence: 83%
“…Because television is often considered a nonveridical source of information (Shrum 2001), television messages may be viewed as weak arguments and thus counterargued rather than endorsed by those high in NFC. Moreover, research has found that NFC tends to be negatively correlated with television viewing (Henning and Vorderer 2001), and study 1 found a similar relation ( , ). Consequently, it is not comr p Ϫ.15 p !…”
Section: Resultsmentioning
confidence: 83%
“…Another example is the notion of escapism that attempts to explicate how media, particularly narratives presented through media, may provide some sort of transient mental retreat for users who feel uncomfortable in their actual lives and social worlds (Henning & Vorderer, 2001;Katz & Foulkes, 1962). Likewise, this research does not explain what those users who escape through exposure to a narrative get in exchange for this.…”
Section: The Complexity Of the Entertainment Experiencementioning
confidence: 95%
“…Escapism is the extent to which the user becomes so absorbed in using an IS that it fulfills his or her desire to 'leave' reality in a cognitive and emotional way [3]. Following Mathwick et al, escapism is an intrinsic value, as it reflects elements of social play; it is an active source of intrinsic value because the user needs to be actively involved with the system to escape from reality.…”
Section: An Integrated Model Of Experiential System Valuementioning
confidence: 99%